Postural defects - kyphosis, lordosis, sway back, flat back. Part two - Piotr Jaworski (Kazimierz Wielki University, 2019)
Posture defects are a serious social problem. It is very important to be able to distinguish between postural defects. A part of the second part of the paper presents a description of kyphosis, lordosis, sway back and flat back.